Penyuluhan Kesehatan Gizi pada Lansia dengan Osteoporosis pada Ibu-Ibu Aisyiyah Pimpinan Daerah Kabupaten Cirebon - Marwati Marwati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Osteoporosis is a common health problem among the elderly, particularly in women, caused by decreased bone mass influenced by age, hormonal changes, lifestyle, nutritional intake, and physical activity. WHO data (2015) shows that the prevalence of osteoporosis in women increases significantly with age, and in Indonesia, the prevalence has reached an alarming level of 19.7% of the population. West Java has recorded an osteoporosis risk of 22.3% (Ministry of Health, 2015). Low calcium intake and lack of physical activity are modifiable factors that can help prevent bone density loss. This health education program aimed to increase the knowledge of Aisyiyah District Leaders in Cirebon Regency regarding osteoporosis in the elderly, its risk factors, prevention strategies, and its impact on joint health. The target participants were pre-elderly and elderly women, especially members of the Branch and District Leaders of Aisyiyah in Cirebon Regency. The method used included lectures and question-and-answer sessions supported by presentation media. Participants’ knowledge was evaluated using oral pre-tests and post-tests. The program outcomes are expected to raise awareness and understanding of the importance of consuming calcium-rich foods, getting adequate sunlight exposure, and engaging in regular physical activity as preventive measures against osteoporosis. Furthermore, this activity plays a role in reducing the incidence of osteoporosis among the elderly through continuous community-based health education.